Regenerating Archives in the Digital Age Between Tradition and Innovation: The Archive of the Capitolo of Laterza - Nicola Barbuti; Stefania Riso (Umanistica Digitale, 2025)
This paper presents the outcomes of the pilot development of a Digital Cultural Monument (DCM) dedicated to archival collections, specifically aimed at digitally regenerating a documentary series related to a centuries-old legal dispute over Civic Uses. Originally, the documentation was hosted in the Archive of the Capitolo of Laterza, but it was subsequently fragmented due to historical and legal events spanning approximately four centuries, from the 17th to the 20th century. Over time, the most substantial part of the documents was incorporated into the private archive of the dell’Aquila Family, while a residual collection of documents is currently preserved in the Archive of the Chiesa Madre di San Lorenzo Martire in Laterza. The project initially focused on digitizing both documentary sets and digitally reconstructing the original archival organization of the documents within the ancient Capitolo Archive. However, direct analysis of the original materials revealed specific characteristics that led to a new perspective on the usability of the digital collection. The study identified fasciculation and cartulation corresponding to document aggregations associated with various phases of the legal dispute. Consequently, the project sought to provide users with access to these individual aggregations by clustering them according to their respective cartulation references. Currently, research is underway to develop potential interface solutions designed to facilitate user access and consultation, ensuring an optimized and intuitive exploration of the reconstructed digital archive.